2010
DOI: 10.1177/1063426609351172
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Behavior Problems in Classroom Social and Learning Situations and Peer Social Competence in Head Start and Kindergarten

Abstract: The relations between early emotional and behavioral problems in classroom situations and peer social competence were examined for a representative sample of urban Head Start children. Behavior problems were assessed within the context of routine peer, teacher, and structured learning classroom situations early in the preschool year. Two path models were tested: (a) direct effects of preschool situational problems on peer social competence at the end of preschool and (b) direct and indirect effects of preschoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 66 publications
3
36
0
Order By: Relevance
“…Social behaviors, including cooperation, emotional aspects of self-control and avoidance of externalizing behaviors are important to a healthy transition into school, as well as to motivation, involvement in learning, and relationships with peers and teachers (Bulotsky-Shearer et al, 2010; Whittaker & Harden, 2010). This study observed that children’s object-manipulation skills have strong relations with development of positive social skills (cooperation, emotional aspects of self-control) and avoidance of negative behaviors (externalizing/hyperactivity) in preschool classrooms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social behaviors, including cooperation, emotional aspects of self-control and avoidance of externalizing behaviors are important to a healthy transition into school, as well as to motivation, involvement in learning, and relationships with peers and teachers (Bulotsky-Shearer et al, 2010; Whittaker & Harden, 2010). This study observed that children’s object-manipulation skills have strong relations with development of positive social skills (cooperation, emotional aspects of self-control) and avoidance of negative behaviors (externalizing/hyperactivity) in preschool classrooms.…”
Section: Discussionmentioning
confidence: 99%
“…Children who exhibit more externalizing behaviors in preschool or elementary school often face challenges establishing positive relationships with peers, teachers (Bulotsky-Shearer, Dominguez, Bell, Rouse, & Fantuzzo, 2010; Whittaker & Harden, 2010), and family members (Larsson, Viding, Rijsdijk, & Plomin, 2008). Young children with externalizing behaviors also show less motivation to learn and fewer positive attitudes about learning in preschool, which is connected to lower achievement in elementary school (McWayne & Cheung, 2009).…”
Section: Relationship Between Object Manipulation Skills and Social Bmentioning
confidence: 99%
“…For example, in a study in a lower-to-middle class sample of kindergarteners and first graders, teacher-rated DB problems negatively predicted peer-rated social preference scores at 1 and 2 years’ follow-up (Schwartz et al 1999). Likewise, in an ethnically diverse sample of boys and girls enrolled in Head Start, teacher ratings of DB problems in preschool predicted (different) teacher ratings of social competence in kindergarten (Bulotsky-Shearer et al 2010). Finally, in one study beginning in toddlerhood, parent-rated DB problems at age 2 were negatively associated with sociometric ratings of liking in kindergarten (Keane and Calkins 2004).…”
Section: Studies Of Db Problems and Social Functioning That Do Not Acmentioning
confidence: 99%
“…Building Empathy 167 associated with externalizing and internalizing difficulties that interfere with children's lives both at home and in school (Bornstein, Hahn, & Haynes, 2010;Bulotsky-Shearer, Domínguez, Bell, Rouse, & Fantuzzo, 2010).…”
mentioning
confidence: 99%